Impact of training on students' knowledge related to chronic energy deficiency - Khalida Fauzia; Imtiyaz Irbatunnisa; Aisyah Nurrohmah; Dian Meidiana (Universitas Pendidikan Indonesia, 2025)
Chronic Energy Deficiency (CED) is a condition where adolescent girls experience prolonged or chronic malnutrition (calories and protein). The prevalence of CED in the Ciparay District, Bandung Regency, falls within the moderate category. SMPIT Thariq Bin Ziyad is located in the Ciparay District, which has a moderate prevalence of CED in Bandung Regency. This community service aims to provide training to junior high school students using lecture and game methods related to Chronic Energy Deficiency and to assess the impact on student knowledge. The methods used are lecture and game methods. Measurement of training indicators was carried out using pre-test and post-test assessments. The participants in this training were 45 students in grades VII-IX. Data analysis used the Wilcoxon signed-rank test. The results of statistical tests on the pre-test and post-test of participants indicated a significant positive increase in knowledge related to CED following the training. Based on the community service carried out, it could be concluded that training using lecture methods and interactive games is effective in improving CED knowledge in students at SMPIT Thariq Bin Ziyad. Abstrak Kekurangan Energi Kronis (KEK) merupakan suatu keadaan remaja putri mengalami kekurangan gizi (kalori dan protein) yang berlangsung secara lama atau menahun. prevalensi KEK di Kecamatan Ciparay, Kabupaten Bandung termasuk pada kategori sedang. SMPIT Thariq Bin Ziyad berada di Kecamatan Ciparay yang memiliki prevalensi KEK dengan kategori sedang di Kabupaten Bandung. Pengabdian masyarakat ini bertujuan untuk memberikan pelatihan kepada peserta didik menengah pertama menggunakan metode ceramah dan permainan terkait Kekurangan Energi Kronis dan melihat dampak pada pengetahuan peserta didik. Metode yang digunakan yaitu metode ceramah dan permainan. Pengukuran indikator keberhasilan pelatihan dilakukan menggunakan pre-test dan post-test. Peserta pelatihan ini adalah peserta didik kelas VII-IX sebanyak 45 orang. Analisis data menggunakan uji Wilcoxon Signed Ranks. Hasil uji statistik terhadap pre-test dan post-test peserta menyatakan secara signifikan bahwa terdapat peningkatan positif pada pengetahuan terkait KEK setelah pelatihan dilakukan. Berdasarkan pengabdian yang dilakukan ini dapat dikatakan bahwa pelatihan menggunakan metode ceramah dan permainan interaktif efektif dalam meningkatkan pengetahuan KEK pada peserta didik di SMPIT Thariq Bin Ziyad. Kata Kunci: Kekurangan Energi Kronik (KEK); kekurangan gizi; metode ceramah; metode permainan; remaja